The Study of Chemical and Sensory Quality of Liang Tea Pontianak Beverages Rich in Antioxidants on Various Concentrations of Sappan Wood (Caesalpinia sappan L.) - Jessy, Jessy Agustina (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Liang tea is a functional drink that acts as an herbal drink in Pontianak. Liang tea drinks are made from different herbal ingredients according to local tastes. Currently, the chemical and sensory qualities of liang tea in Pontianak do not yet exist, so the taste, color and chemical content variety depending on the producen. One of the materials that can be used in making tea drink is sappan wood. The purpose of this study was to obtain the concentration of sappan wood on herbal ingredients that could produce the best chemical and sensory quality characteristics of liang tea Pontianak drink. This study used a single factor randomized block design, namely the addition of sappan wood which consisted of 5 treatment levels ( 0% ; 4% ; 8% ; 12% ; 16%) with 5 replications. The data obtained were analyzed using 5% ANOVA, with further testing using the 5% level BNJ test. The best treatment was using the effectiveness index test. The results showed that the best treatment was obtained with the addition of 8% sappan wood. The chemical characteristics of the best liang tea Pontianak drink produced total flavonoids (3344.31 mg QE/ 100g), antioxidants (41.53%) and vitamin C content 3.96 mg/ 100 mL. The best sensory test results are color (70.00), aroma (80.00) and taste (81.00).